A CASE STUDY ON THE OPERATION AND MARKETING STRATEGIES OF GROUP HOME IN JAPAN - Lin, Linda Lin-Chin; Lu, Shu-Fen; Huang, Chen-Zhen (Graduate Program of Universitas Tarumanagara, 2024)
This study uses the Sky Group Home case study method to understand the current status of the industrial environment where the case is located, and explore the development trends and business strategies of Japanese companies in the group home market. It also analyses the corresponding marketing strategies of the industry based on regional expansion points, so as to improve the competitiveness of the industry's regional channels and open up new markets for international group home development. In recent years, Taiwan's group homes have been gradually privatized, and Japan's implementation experience has a high degree of reference value for my country's policy construction and group homes. This study focuses on operating groups in Japan Company A of Home House is taken as the research object, and the standard policies and operating models for the establishment of Japanese group homes are discussed through literature. Company A is used to understand its operating model based on its service content and current operating conditions. Environmental analysis and marketing mix analysis are conducted to explore its market, management and Marketing strategy; Finally, use SWOT analysis to summarize A The current situation of the company and suggestions for the future development of the industry. The legal entity creates a daily life environment similar to home, adhering to the core concept of